2017
DOI: 10.1007/978-3-662-54434-1_26
|View full text |Cite
|
Sign up to set email alerts
|

The Essence of Higher-Order Concurrent Separation Logic

Abstract: Abstract. Concurrent separation logics (CSLs) have come of age, and with age they have accumulated a great deal of complexity. Previous work on the Iris logic attempted to reduce the complex logical mechanisms of modern CSLs to two orthogonal concepts: partial commutative monoids (PCMs) and invariants. However, the realization of these concepts in Iris still bakes in several complex mechanisms-such as weakest preconditions and mask-changing view shifts-as primitive notions.In this paper, we take the Iris story… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(105 citation statements)
references
References 38 publications
1
104
0
Order By: Relevance
“…Higher-order concurrent separation logic [Jung et al 2015;Krebbers et al 2017] can express ghost state within the assertion language of the logic itself. This feature can be used to eliminate the restriction of RGSep[FI] that the semantics of the flow interface predicates is defined on the meta level and that it does not support nesting of flow interface abstractions (i.e., cases where a node of a flow graph should abstract from another flow graph contained in the node).…”
Section: Related Workmentioning
confidence: 99%
“…Higher-order concurrent separation logic [Jung et al 2015;Krebbers et al 2017] can express ghost state within the assertion language of the logic itself. This feature can be used to eliminate the restriction of RGSep[FI] that the semantics of the flow interface predicates is defined on the meta level and that it does not support nesting of flow interface abstractions (i.e., cases where a node of a flow graph should abstract from another flow graph contained in the node).…”
Section: Related Workmentioning
confidence: 99%
“…For reasons of space, we cannot explain all of Iris. We refer the reader to the Iris papers and manual [37,38,41, 59] for a full account. Instead, we will just describe some essential aspects needed to understand our extensions and examples.…”
Section: Background On Irismentioning
confidence: 99%
“…Technically, these works are based on "non-standard models" of SL, different from the heaplet model but instances of Pym's resource semantics as in Figure 2; see Pym et al 36 There are many such models, including ones incorporating read and other permissions, 7 auxiliary state, 39 time, 39 protocols, 29 and others. Abstract SL 13 showed how general program logic could be defined based on these models, and the works just mentioned and others showed that some of them had surprising ramifications.…”
Section: Abstraction and The Fiction Of Separationmentioning
confidence: 99%